Role of curvature in controlling SWBLI behavior in a hypersonic double ramp flow - Aggarwal, Abhinav; Ranjan, Rajesh (Frontiers in Mechanical Engineering, 2025)
Hypersonic flows generate intense unsteady pressure and thermal loads, posing significant challenges for high-speed aerospace applications such as re-entry vehicles and hypersonic cruise systems. These extreme conditions necessitate effective flow control strategies to enhance aerodynamic performance and structural integrity. This study examines the influence of surface curvature on these loads in a double-wedge geometry, aiming to optimize flow control approaches. Unsteady Mach 7 flow simulations are conducted using a high-fidelity, time-accurate solver with third-order MUSCL as well as seventh-order WENO schemes, ensuring precise resolution of shock interactions and flow structures. A standard double-ramp configuration is analyzed alongside two smooth ramp configurations, where the faceted intersection of the front and aft wedges is replaced with different curvature levels. The computational results are validated against experimental heat-flux data to confirm the accuracy of the numerical approach. The findings reveal that the high-curvature geometry (curvature, κ=1.01) introduces only marginal variations in mean pressure and thermal loads. However, transient flow characteristics are notably altered. In contrast, the low-curvature configuration (κ=0.49) significantly reduces both pressure and thermal loads by 43% and 58%, respectively, while also minimizing the separation region. The reduced separation leads to a smoother and more stable flowfield, contributing to improved aerodynamic efficiency. Long-term analysis further indicates that the low-curvature configuration accelerates the decay of large-amplitude unsteady signals, suggesting enhanced flow stability over extended durations. These results underscore the potential benefits of surface curvature in mitigating aerodynamic heating and structural stresses in hypersonic flows, and therefore provide insights for the development of more efficient hypersonic vehicles with improved thermal management, enhanced vehicle survivability, and better overall performance in extreme flight conditions.